Secondary Metabolites and Cytotoxicity of Kitolod Leaf Extract (Hippobroma longiflora (L.) G. Don to Shrimp Larvae (Artemia salina Leach): Metabolit Sekunder dan Sitotoksisitas Ekstrak Daun Kitolod (Hippobroma longiflora (L.)) terhadap Larva Udang (Artemia salina Leach) - Ibrahim, Arsyik; Bulan, Adisty Sindi; Ramadhan, M. Rahmad; Bone, Mahfuzun; Rija'i, Hifdzur Rashif; Rusman, Arman; Arifuddin, M.; Junaidin, Junaidin; Rijai, Laode (Jurnal Riseta Naturafarm, 2025)
One of the plants used by the people of East Kalimantan, especially the people of West Kutai, as a medicinal plant is Kitolod (Hippobroma longiflora L.). The plant parts used are the leaves and flowers. The secondary metabolites contained in Kitolod leaves are alkaloids, saponins, flavonoids and polyphenols. The aim of this research is to identify secondary metabolite groups and test the cytotoxicity of Kitolod leaf extracts and fractions. Secondary metabolites are identified qualitatively using various chemical reagents and metabolites characterized by the presence or absence of color changes or the presence of sediment or foam. Cytotoxicity testing was carried out using the Brine Shrimp Lethality Test (BSLT) method. The data research was analyzed using the Reed and Muench method to determine the Lethality Concentration 50% value. The results of research on the metabolite content of ethanol extract, fractions: n-hexane, ethyl acetate and n-butanol contain alkaloid, flavonoids and phenolic/polyphenols compounds. The bioactivity test results for the ethanol extract had an LC50 value of 592.93 ppm, the n-hexane fractions of 582.77 ppm, the ethyl acetate fraction of 531.37 ppm, and the n-butanol fraction of 119.48 ppm. These results indicate that the n-butanol fraction of Kitolod leaves has stronger cytotoxic activity than other extracts. .